A critical review of the role of responsive curricula in optimising learning in higher education - Human-Hendricks, N.E.; Meier, C. (South African Journal of Higher Education, 2020)
Higher education institutions are expected to heighten their responsiveness to societal interests and needs, and to the world of work, by improving on their curricula. In answering the call for greater responsiveness, basic and higher education institutions in South Africa have introduced a paradigm shift from content- to outcomes-based education. The focus of this article is to present a critical analysis of the extant literature on the nature and role of responsive curricula in optimising learning in higher education. To this end, the researchers adopted an interpretative approach and descriptive perspective. Data were collected by consulting primary and secondary sources during a literature review. The findings revealed that there is a dynamic yet complex relationship between a responsive curriculum and the optimisation of learning. The literature indicated that, having undertaken to make this a central issue in their policies, the majority of institutions of higher learning are still grappling with what exactly constitutes a responsive curriculum, let alone what the implementation thereof will entail.